Establishment of economic injury levels for olive infestation by Dαcus oleαe, in Corfu - Kapatos, Ε.Τ.; Fletcher, B.S. (ENTOMOLOGIA HELLENICA, 1983)
Economic injury levels for cover sprays and air bait sprays were established for the infestation by Dacus oleae (Gmelin) (Diptera: Tephritidae). For cover sprays, the economic injury levels (expressed as percent infestation by taking 30,000 fruits to represent the average number of fruits per tree) were calculated as 7.59% for infestation laid in late July-August, 6.16% for infestation in September and 10.31% for infestation in October. For air bait sprays, economic injury levels were calculated for various fruiting conditions (expressed as proportion of trees bearing olive fruits) and they were much lower than for cover sprays due to the lower cost of air treatments. For July-August, they ranged from 5.07% infestation for 25% trees bearing olives to 1 .27% for 100% trees with olive fruits. For September they ranged from 4.11% to 1.08% infestation, for October they ranged from 6.88% to 1 .72% infestation and for infestation laid in November they ranged from 61.28% to 15.32% infestation, respectively. The economic injury levels for air bait sprays were also expressed as mean weekly number of females per McPhail trap by taking into account the potential fecundity of D. oleae and the efficiency of the McPhail trap (baited with protein hydrolysate 2% and borax 1 .5%) at different times of the year. For September, they ranged from 16 females per trap for groves with 25% of trees bearing olive fruits, to 4 females per trap for 100% trees with fruits. For October, they ranged from 6 females per trap to I female per trap, respectively.